ASEAN and thai rubber industry labor mobility determinants: A structural equation model - Nobnorb, Preecha; Fongsuwan, Wanno (My University, 2015)
The ASEAN rubber industry is in a state of crisis with prices in a continuing three year downward spiral but over the horizon is the 2015 AEC integration date promising closer integration, reduction of tariffs and the freer mobility of labor. This research therefore undertook a structural equation model to study and identify the determinants of ASEAN and Thai labor mobility of which 1 million families or more than 6 million people are dependent on rubber production while another 4.8 million households or 18 million people are dependent on rice farming which are both highly intensive foreign labor endeavors. The study revealed that the vast majority of Thai expatriates who choose foreign work have a very positive experience who state that foreign work should be supported by the government. For the structural equation model, 340 rubber industry management staff were queried using both quantitative and qualitative research tools including PLS-Graph software for qualitative analysis of in-depth interviews from 10 senior level executives involved in corporate policy. From the research it was determined that skill levels have a direct and positive influence on labor mobility and the factors that have the maximum overall positive influence are migration pull and push factors. Government labor policies include foreign worker and labor law policies which have both a direct and indirect effect on labor mobility. Although the rubber industry is in an extended period of falling prices, new applications and sectors are being explored, such as rubber use in road construction.
Keywords: ASEAN; Government labor policies; Labor mobility; Labor relations; Labor skills; Thailand